ANALISIS ANAK PENDIDIKAN DASAR PUTUS SEKOLAH DI DESA BENGLE KECAMATAN MAJALAYA KABUPATEN KARAWANG - Muhammad Majid Ramadhan; Anggy Giri Prawiyogi; Sinta Maria Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the factors causing and impact of dropping out of school on children in Bengle Village, a village located in a rural area. Research subjects were parents, children who had dropped out of school, and village officials for the 2023/2024 academic year. The method used in this research is a qualitative approach with in-depth interview techniques and participant observation. Data was collected through interviews with parents, children who had dropped out of school, and village officials, as well as direct observation of school and household conditions. The research results show that the main factors causing school dropout include family economic problems, lack of access to adequate educational facilities, and low awareness of the importance of education. The impacts of dropping out of school include reduced future employment opportunities, as well as increased social and economic risks. This research suggests the need for more holistic interventions from the government and educational institutions to address this problem, including financial assistance programs, improving educational facilities, and awareness campaigns about the importance of education among the community Keywords: Children out of school